2012
DOI: 10.1103/physrevb.86.125431
|View full text |Cite
|
Sign up to set email alerts
|

Charge impurity as a localization center for singlet excitons in single-wall nanotubes

Abstract: A simple model is developed for studying the interaction of bright excitons in semiconducting single-wall nanotubes with charged impurities. The model reveals red shift in the energy of excitonic states in the presence of impurity, thus indicating binding of free excitons in the impurity potential well. Several bound states were found in absorption spectrum below the onset of excitonic optical transitions in the bare nanotube. Dependence of the binding energy on the model parameters, such as impurity charge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…2), we reject the hypothesis of defect-localized excitonic states 12 . However, both theoretical 21 and experimental 22 studies have shown that excitons may localize due to the impact of ions adsorbed on the surface of SWNTs, even without covalent bonds. Thus, one should ascribe the X energy level either to the hole-polaron-dressed exciton or to the excitons localized on the sites of physically adsorbed H + ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), we reject the hypothesis of defect-localized excitonic states 12 . However, both theoretical 21 and experimental 22 studies have shown that excitons may localize due to the impact of ions adsorbed on the surface of SWNTs, even without covalent bonds. Thus, one should ascribe the X energy level either to the hole-polaron-dressed exciton or to the excitons localized on the sites of physically adsorbed H + ions.…”
Section: Resultsmentioning
confidence: 99%
“…A theoretical investigation by Tayo at al. indicated that charged particles, physisorbed on the surface of SWNTs, might play the role of localization centres for excitons 21 . It was also found experimentally in electrochemically doped nanotubes that both excitons and trions are spatially confined because of adsorbed ions, even without chemical bonding with the nanotube wall 22 .…”
Section: Introductionmentioning
confidence: 99%
“…5(b)) 15 . Qualitatively, the wave-functions of the excitons belonging to different subbands differ only by the extension of the bound relative motion along the tube axis and by a subbanddependent circumferential phase (related to the pseudo angular momentum) 41 . However, the matrix element of the Coulomb interaction is insensitive to the phase factors (the angular momentum is conserved separately for each exciton in either intraband and crossed scatterings since in both cases pictured in Fig.…”
Section: B Broadeningmentioning
confidence: 99%
“…The finite temperature DOS per electron of the infinite periodic (p) system ρ p (E) is given by: 45,46 …”
Section: Resultsmentioning
confidence: 99%